Improving Speech Perception in Noise for Children with Cochlear Implants. - Gifford, René H.; Olund, Amy P.; DeJong, Melissa (Journal of the American Academy of Audiology, 2011)
Background: Current cochlear implant recipients are achieving increasingly higher levels of speech recognition; however, the presence of background noise continues to significantly degrade speech understanding for even the best performers. Newer generation Nucleus cochlear implant sound processors can be programmed with SmartSound strategies that have been shown to improve speech understanding in noise for adult cochlear implant recipients. The applicability of these strategies for use in children, however, is not fully understood nor widely accepted. Purpose: To assess speech perception for pediatric cochlear implant recipients in the presence of a realistic restaurant simulation generated by an eight-loudspeaker (R-SPACE™) array in order to determine whether Nucleus sound processor SmartSound strategies yield improved sentence recognition in noise for children who learn language through the implant. Research Design: Single subject, repeated measures design. Study Sample: Twenty-two experimental subjects with cochlear implants (mean age 11.1 yr) and 25 control subjects with normal hearing (mean age 9.6 yr) participated in this prospective study. Intervention: Speech reception thresholds (SRT) in semidiffuse restaurant noise originating from an eight-loudspeaker array were assessed with the experimental subjects' everyday program incorporating Adaptive Dynamic Range Optimization (ADRO) as well as with the addition of Autosensitivity control (ASC). Data Collection and Analysis: Adaptive SRTs with the Hearing In Noise Test (HINT) sentences were obtained for all 22 experimental subjects, and performance--in percent correct--was assessed in a fixed +6 dB SNR (signal-to-noise ratio) for a six-subject subset. Statistical analysis using a repeated-measures analysis of variance (ANOVA) evaluated the effects of the SmartSound setting on the SRT in noise. Results: The primary findings mirrored those reported previously with adult cochlear implant recipients in that the addition of ASC to ADRO significantly improved speech recognition in noise for pediatric cochlear implant recipients. The mean degree of improvement in the SRT with the addition of ASC to ADRO was 3.5 dB for a mean SRT of 10.9 dB SNR. Thus, despite the fact that these children have acquired auditory/ oral speech and language through the use of their cochlear implant(s) equipped with ADRO, the addition of ASC significantly improved their ability to recognize speech in high levels of diffuse background noise. The mean SRT for the control subjects with normal hearing was 0.0 dB SNR. Given that the mean SRT for the experimental group was 10.9 dB SNR, despite the improvements in performance observed with the addition of ASC, cochlear implants still do not completely overcome the speech perception deficit encountered in noisy environments accompanying the diagnosis of severe-to-profound hearing loss. Conclusion: SmartSound strategies currently available in latest generation Nucleus cochlear implant sound processors are able to significantly improve speech understanding in a realistic, semidiffuse noise for pediatric cochlear implant recipients. Despite the reluctance of pediatric audiologists to utilize SmartSound settings for regular use, the results of the current study support the addition of ASC to ADRO for everyday listening environments to improve speech perception in a child's typical everyday program.